PREPERATION AND CHARACTERIZATION OF β-CYCLODEXTRIN INCLUSION COMPLEXES ORAL TABLETS CONTAINING POORLY WATER SOLUBLE GLIMIPIRIDE USING FREEZE DRYING METHOD - Yandi Syukri; Laryssa Fernenda; Fissy Rizki Utami; Isna Qiftayati; Aris Perdana Kusuma; Rochmy Istikaharah (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Glimepiride is an oral antidiabetic drugs which is practically insoluble in water. The formation of β-cyclodextrin inclusion complex was able to increase the solubility of glimepiride. This study aim to prepare, characterize and formulation of inclusion complex tablets in order to meet the requirement in Pharmacopeia. The inclusion complex were prepared in a molar ratio of 1:1 and 1:2 by freeze drying method, afterthat characterized include FTIR spectroscopy and scanning electro microscope (SEM). Further, it was formulated into tablets by direct compression technique using primogel and crospovidone as superdisintegrants. The tablets were evaluated include weight uniformity, hardness, friability, disintegration, and dissolution. The dissolution studies of inclusion complex were performed by using USP II apparatus. The result of FTIR and SEM provided evidence of the formation of complexes after utilizing freeze-drying methods. The tablet evaluation containing inclusion complex glimepiride-β cyclodextrin with primogel and cropovidone as disintegrant showed that increased concentration of disintegrant will increase disintegration time of the tablets. All of formulas meet the requirements in the Pharmacopoeia. The inclusion complex of glimepiride–β cyclodextrin successfully used for enhancing the solubility of glimepiride and the tablets meet the requirement in Pharmacopeia.Keywords: Glimepirid, β-cyclodextrin, primogel, crospovidone